Mapping of immunogenic regions of human T cell leukemia virus type I (HTLV-I) gp46 and gp21 envelope glycoproteins with env-encoded synthetic peptides and a monoclonal antibody to gp46 - Palker, TJ; Tanner, ME; Scearce, RM; Streilein, RD; Clark, ME; Haynes, BF (The Journal of immunology (1950), 1989)
Antigenic sites on human T cell leukemia virus type I (HTLV-I) gp46 and gp21 envelope glycoproteins that are immunogenic in man were studied with envelope gene (env)-encoded synthetic peptides and a mAb to HTLV-I gp46 envelope glycoprotein. Antibodies in 78% of sera from HTLV-I seropositive subjects reacted with synthetic peptide 4A (amino acids 190 to 209) from a central region of HTLV-I gp46. Human anti-HTLV-I antibodies also bound to synthetic peptides 6 (29% of sera) and 7 (18% of sera) from a C-terminal region of gp46 (amino acids 296 to 312) and an N-terminal region of gp21 (amino acids 374 to 392), respectively. mAb 1C11 raised to affinity-purified HTLV-I gp46 reacted with gp46 external envelope glycoprotein and gp63 envelope precursor in immunoblot assay and also bound to the surface of HTLV-I+ cells lines HUT-102 and MT-2. Antibody 1C11 did not react with HTLV-II or HIV-infected cells or with a broad panel of normal human tissues or cell lines. In competitive RIA, anti-gp46 antibody 1C11 was inhibited from binding to gp46 either by antibodies from HTLV-I seropositive subjects or by HTLV-I env-encoded synthetic peptide 4A, indicating that 1C11 bound to or near a site on gp46 within amino acids 190 to 209 also recognized by antibodies from HTLV-I-seropositive individuals. When tested in syncytium inhibition assay, mAb 1C11 did not neutralize the infectivity of HTLV-I. Thus, HTLV-I infection in man is associated with a major antibody response to a region of gp46 within amino acids 190 to 209 that is on the surface of virus-infected cells.